Voicing the void muteness and memory in Holocaust fiction - Horowitz, Sara R. (SUNY series in modern Jewish literature and culture, 1997)
Through new close readings of Holocaust fiction, this book takes the field of Holocaust Studies in an important new direction. Reading a wide range of narratives representing different nationalities, styles, genders, and approaches, Horowitz demonstrates that muteness not only expresses the difficulty in saying anything meaningful about the Holocaust - it also represents something essential about the nature of the event itself. The radical negativity of the Holocaust ruptures the fabric of history and memory, emptying both narrative and life of meaning. At the heart of Holocaust fiction lies a tension between the silence that speaks the rupture, and the narrative forms that attempt to represent, to bridge it.